Propiedades Termodinámicas del Efecto Hidrofóbico en la Estabilidad Proteica - Espinosa Silva, Yanis Ricardo (2015)
When we talk about protein denaturation remember the Levinthal paradox and recognize that the age of the universe is not enough to sample the probability of structural conformations that may choose a protein. Withthe advancement of the experimental techniques we determine structural states of the protein conformation, even more cannot be predicted from a linear sequence of amino acids which will be functional 3D structure. Some authors propose that beyond the importance of protein-protein interactions are interactions with waterwho completing tertiary functional organization and non-covalent forces such as hydrophobic effect and van ders Waals interactions could have an effect mediate synergistic native minimum energy conformationsof a protein